Environmental Contaminants and Human Health: The Health Effects of Persistent Toxic Substances - Carpenter, David O. (Fırat University, 2005)
Chemical contaminants are widespread in our environment, and we all carry some of many different chemicals in our bodies. What these chemicals do to our health is a very important question. While many chemicals can cause harm to humans, we know much about two categories of persistent toxic substances, metals such as lead and mercury and organohalogens, such as polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs). These substances are very persistent in the environment and in the human body, and can increase risk of a variety of diseases. It is imperative that we find ways of removing these dangerous chemicals from the environment and ways of reducing human exposure.

Doğada yaygın biçimde bulunan çok sayıdaki kimyasal kirleticilerden bazılarını vücudumuzda da taşırız. Bu kimyasal maddelerin sağlığımızı ne şekilde etkiledikleri çok önemli bir sorudur. Birçok kimyasal madde insan sağlığına zarar verebiliyorken, bizler kalıcı özellik arz eden iki grup kirletici hakkında daha fazla bilgiye sahibiz: kurşun ve cıva gibi metaller ve poli klorlu bifeniller (PCBs) ve poli bromlu difenil eterler (PBDEs) gibi organohalojenlerdir. Bu maddeler doğada ve insan vücudunda çok uzun süre kalabilir ve birçok hastalığın riskini arttırabilirler. Çevrenin bu tehlikeli kimyasal maddelerden arındırılması ve insan maruziyetinin azaltılması için çözümler bulmak zorundayız.
Çevresel Kirleticiler ve İnsan Sağlığı: Kalıcı Toksik Maddelerin Sağlığa Zararları